Students’ Interest in Using the Shadowing Technique for Pronunciation Skills - Ricky Dian Saputra; Yani Lubis (MASI Mandiri Edukasi, 2026)
This study aims to determine students' interest in using the shadowing technique to improve pronunciation skills in English language learning. The shadowing technique, which requires students to listen and simultaneously imitate the speech of native speakers, is considered an effective approach to improve pronunciation accuracy, fluency, and self-confidence. This study used a qualitative descriptive method involving 25 seventh-grade students at MTS Swasta Al-Anshor Perdagangan II. Data were collected through a closed-ended questionnaire with a four-point Likert scale designed to measure students' perceptions, attitudes, and interests toward the application of the shadowing technique. The results showed that most students had a high level of interest and positive attitudes toward the use of shadowing in pronunciation learning. The majority of students stated that this technique helped improve speaking fluency, self-confidence, and enjoyment in learning English. Although some students had difficulty keeping up with the pace of native speakers, they still considered shadowing a useful and interesting method. These findings suggest that the integration of the shadowing technique in pronunciation teaching can encourage active learning, independent learning, and continuous improvement in students' speaking skills.